Physical Growth Status and Feeding Methods of Chinese Infants With Cleft Lip With or Without Cleft Palate Under 1 Year of Age - Wu, Wenli; Sun, Jing; Liu, Huiyan; Chen, Biting; Gao, Zijun; Chen, Yiyang; Li, Fan; Wang, Hongtao (Frontiers in Pediatrics, 2020)
Objectives: Malnutrition is a characteristic feature of cleft lip with or without palate (CL/P). This study aims to retrospectively quantify the physical growth status, evaluate the feeding methods, and identify the possible correlation of CL/P types with growth failure. Methods: The length and weight of 508 infants with CL/P and 118 healthy infants were recorded at the date of admission. The weight-for-age (W/A), length-for-age (L/A), and body mass index-for-age (BMI) of the infants were calculated. Results: The L/A values were significantly lower in the infants with cleft lip (CL, 123 cases) and cleft lip with palate (CLP, 122 cases) than those of the control infants (p ˂ 0.01). The W/A values of the infants with CP (263 cases) and CLP were significantly lower than those of the control infants (p ˂ 0.05). However, the BMI index was not significantly different between any of the studied groups and the controls. In the mixed feeding group, the infants with CL and CP showed significantly lower L/A (p ˂ 0.05) and W/A (p ˂ 0.05), respectively. Conclusion: Physical growth issues were more common in the infants with CP and CLP. Because this was a retrospective study, the foods supplied to the patients were not strictly uniform, therefore, a prospective study with unified food supplement may be needed to confirm these findings.